Implementasi Algoritma Kriptografi AES untuk Keamanan Data pada Aplikasi Pesan Instan Berbasis Android - Arek Satria; Bagas Piwari; Tata Sutarbi (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
This study uses AES-256 encryption to protect data in Android messaging apps. The algorithm works well, encrypting text messages in 0.05 seconds and multimedia files in 0.2 seconds, without affecting device resources. Testing confirms that AES-256 effectively protects user data while maintaining communication capabilities in real time. These findings provide valuable insights for developers seeking to enhance data protection in instant messaging platforms without compromising user experience. The solution offers an optimal balance between security and performance for mobile applications.